Robotic Surgery for Giant Presacral Dumbbell-Shape Schwannoma - Farid Yudoyono; Muhammad Zafrullah Arifin; Rully Hanafi Dahlan; Sevline Estethia Ompusunggu; Shin Dong Ah; Yi Seong; Ha Yoon; Yoon Do Heum; Kim Keung Nyun (Faculty of Medicine Universitas Padjadjaran, 2015)
Objective: To demonstrate the feasibility of using da Vinci robotic surgical system to perform spinal surgery.Methods: Magnetic resonance imaging (MRI) of a 29-year-old female patient complaining right pelvic pain for 1 month revealed a 17x8x10 cm non-homogeneous dumbbell shape encapsulated mass with cystic change located in the pelvic cavity and caused an anterior displacement of urinary bladder and colon.Results: There was no systemic complication and pain decrease 24 hours after surgery and during 2 years of follow up. The patient started a diet 6 hours after the surgery and was discharged 72 hours after the surgery. The pathological diagnosis of the tumor was schwannoma. Conclusions: Giant dumbbell shape presacral schwannomas are rare tumours and their surgical treatment is challenging because of the complex anatomy of the presacral. Clinical application of da Vinci robotic surgical system in the spinal surgical field is currently confined to the treatment of some specific diseases or procedures. However, robotic surgery is expected to play a practical future role as it is minimally invasive. The advent of robotic technology will prove to be a boon to the neurosurgeon.Keywords: da Vinci robotic surgical system, presacral, schwannoma DOI: 10.15850/ijihs.v3n1.407